Quantum mechanics - Everitt, Mark Julian; Bjergstrom, Kieran Niels; Duffus, Stephen Neil Alexander (Wiley, 2024)
"Quantum mechanics is an integral part of every physics curriculum and one of the most challenging subjects for students because of its fundamentally non-classical concepts. Plus, quantum mechanics requires a demanding, but necessary, mathematical formalism even for seemingly simple problems. On the other hand, it is a fascinating and important subject without which modern science would be unthinkable. And not the least, understanding the concepts of quantum mechanics is essential for studies in atomic and nuclear physics or solid state physics."-- Provided by publisher.